Enhancing User Engagement in the Mobile App: An Agile Approach to New Product Development in the Queue App - Crnogaj, Katja; Gajšt, Nataša (Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024, 2024)
This case study examines the application of new product development (NPD) methodologies within the mobile application industry, focusing on the Queue app – a platform designed for social content discovery and sharing among movie and TV show enthusiasts. Despite initial success, the app encountered challenges in user engagement, social interaction, and retention. The study details the iterative process undertaken by the product team, guided by the NPD principles, to identify, prototype, and implement a new feature, ˈSwipe with Friends.ˈ This feature was designed to address the identified issues by transforming content selection into an interactive and social experience, ultimately leading to significant improvements in user metrics. The case provides insights into how theoretical frameworks in NPD can be practically applied to enhance user engagement and retention in a highly competitive digital landscape.